Nanoscale imaging of photonic and energy transfer processes in photocatalytic nanomaterials - Lustig, Danielle, author; Sambur, Justin, advisor; Krummel, Amber, committee member; Van Orden, Alan, committee member; Gelfand, Martin, committee member (Colorado State University. Libraries, 2025)
With the increasing demand for renewable energy, there is an urgent need to develop advanced materials that enhance solar energy conversion and photoelectrochemical reactions. This research addresses these challenges by investigating semiconductor nanomaterials, particularly hybrid molecule-nanocrystal composites, for next-generation photocatalysis and hydrogen production. This work focuses on two key strategies to improve light-harvesting efficiency: defect-mediated energy transfer and photon recycling. Chapters 1 through 5 explore defect-mediated energy transfer using zinc oxide nanocrystals coupled to molecular dye acceptors. Chapter 2 introduces defect-mediated energy transfer at the ensemble-level, while Chapter 3 introduces single-molecule microscopy as a tool to spatially resolve active donor–acceptor pairs and highlights the development of a single-molecule fluorescence microscopy imaging methodology to study defect-mediated energy transfer. Chapter 4 investigates single-molecule measurements of zinc oxide nanocrystal/dye conjugates, revealing how sample heterogeneity impacts energy transfer efficiency, and Chapter 5 discusses future directions to measure the defect donor transition dipole moment. Chapter 6 investigates photon recycling within nanostructured photoanode systems, where emitted photons are reabsorbed locally as a method to improve solar-to-hydrogen efficiency via a correlative widefield microspectroscopy approach. Lastly, Chapter 7 explores using single-molecule fluorescence microscopy to investigate the binding behavior of methyl viologen on the surface of single CdSe/CdS quantum dots via analysis of fluorescence blinking. Altogether, this dissertation advances the understanding of both photonic and energy transfer mechanisms in photocatalytic nanomaterials. By integrating spectroscopic and single-particle techniques, it lays the foundation for designing hybrid nanomaterials with optimized energy flow and charge dynamics. This research paves the way for designing next-generation materials and technologies to address the pressing need for sustainable energy solutions.
Keywords: FRET; nanocrystals; photocatalysis; microscopy; energy transfer; nanomaterials